Analisis Peluang, Ancaman, Kekuatan, dan Kelemahan Usaha Arch Barbershop di Kota Maumere (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the opportunities, threats, strengths, and weaknesses of Arch Barbershop, a modern barbershop in Maumere City. The study was conducted using a descriptive approach through observation of the business environment, competitor analysis, and identification of local consumer preferences. The analysis shows that Arch Barbershop has promising opportunities due to the increasing trend of grooming among teenagers and young adults, and the lack of barbershops offering modern and consistent service concepts in the area. However, this business also faces threats in the form of competition from new barbershops, rapidly changing consumer preferences, and dependence on barber skills as the spearhead of service quality. Furthermore, internal weaknesses such as limited space, inflexible operating hours, and a less than optimal variety of services pose challenges to business development. By understanding these opportunities, threats, strengths, and weaknesses, Arch Barbershop can formulate a more effective development strategy to increase its competitiveness and business sustainability in Maumere City.